Mathematical aspects of calibration by diffeomorphisms - Orozco, Roberto; Ratajczak, Joanna (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we present a novel approach to calibrating robotic manipulators-calibration by diffeomorphisms. The method is carried out in detail, placing special emphasis on the mathematical basis of the algorithm. The main idea is based on the synergy of the theory of singular mappings and the large dense diffeomorphic metric mapping framework, a method previously unused in robotic applications, together with reproducing kernel Hilbert spaces.
Keywords: kinematics; robot kinematics calibration; diffeomorphisms; calibration by diffeomorphisms